An Analysis of Norm Strata in the Collection of Poetry Deru Campur Debu by Chairil Anwar an Approach to Structuralism - Rosary Iriany; Nuzul Tenriana (Edumaspul: Jurnal Pendidikan, 2022)
The aims of this study to (1) describe the use of norm strata in Chairil Anwar’s collection of poetry Deru Campur Debu, (2) describe the meaning of the use of norm strata analysis in Chairil Anwar's collection of poetry Deru Campur Debu. This research is a type of descriptive analysis. In this study, reading and note-taking techniques was employed in obtaining the data. The data analysis techniques used are heuristic and hermeneutic.The results of the study showed that the five layers of norms in the poetry Deru Campur Debu by Chairil Anwar were one interconnected unit. The dominant sound layer in the poetry Deru Campur Debu were the a and u assonance. The layers of meaning in a collection of poetry contains stories about struggle, love, divinity, and tragedy in human life. The intrinsic and extrinsic layers in the poetry Deru Campur Debu were the setting of time and atmosphere. The layers of the world described in the collection of poetry were spirit, independent, generous, loyal people. The meaning of the poetry Deru Campur Debu were to invite the reader to be enthusiastic in the struggle, get closer to God, not give up in findingthe goals, give sincere love, self-reflection, solidarity, and always be consistent in making decisions.Based on the results of this study, hopefully further researchers can review more expansive by using other approaches, both stylistic and semiotic approaches.